In vitro investigation of hyaluronan-based polymeric micelles for drug delivery into the skin: The internalization pathway - Starigazdová, Jana; Nešporová, Kristina; Čepa, Martin; Šínová, Romana; Šmejkalová, Daniela; Huerta-Angeles, Gloria; Velebný, Vladimír (European journal of pharmaceutical sciences, 2020)
In our previous research, we concluded that polymeric micelles based on hyaluronic acid are able to penetrate into the deeper layers of skin tissue. The aim of this work was to characterize the mechanisms involved in the uptake by skin cells, which is important for understanding the influence of the carrier composition on the drug penetration. To reach this goal, we used micelles encapsulating curcumin made of oleyl-hyaluronan (HAC18:1) and hexyl-hyaluronan (HAC6) covalently linked with fluorescent Nile Blue. This labeling enabled us to track the micelle-forming derivative and also micelle payload into the keratinocytes and fibroblasts by fluorescent microscopy and flow cytometry. The regulation of both the passive and active cellular uptake was used to determine the mechanism of micelle internalization. Furthermore, the changes of membrane fluidity were measured for these derivatives by FRAP. Using these methods we concluded that carriers entered the cells using both active and passive transport. Passive transport was facilitated by the affinity of the carrier to the cell membrane, especially in the case of HAC18:1 carrier, which changed significantly the membrane fluidity. The active transport was dependent on cell type, but mainly driven by the clathrin-mediated endocytosis and macropinocytosis. Surprisingly, the main HA receptor, CD44, was not involved in the uptake. We can conclude that these carrier systems could be used for the local transport of active substances or hydrophobic drugs into the skin cells using the advantage of passive transport of oleyl-HA derivative.
Keywords: Skin cells; keratinocyty; Lysosomes; Hyaluronan; Keratinocytes; Curcumin; lyzozomy; Fibroblasts; kurkumin; Skin Absorption; Polymers; lidé; kůže; kyselina hyaluronová; kožní absorpce; fibroblasty; kultivované buňky; Polymeric micelle; Hyaluronic Acid; endocytóza; Cells, Cultured; Administration, Topical; Cellular transport; aplikace lokální; Skin; Drug Delivery Systems; polymery; Endocytosis; lékové transportní systémy; Humans